2022
DOI: 10.3390/cancers14235901
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Adrenocortical Carcinoma: From Symptoms Control to Palliative Care

Abstract: The prognosis of patients with advanced adrenocortical carcinoma (ACC) is often poor: in the case of metastatic disease, five-year survival is reduced. Advanced disease is not a non-curable disease and, in referral centers, the multidisciplinary approach is the standard of care: if a shared decision regarding several treatments is available, including the correct timing for the performance of each one, overall survival is increased. However, many patients with advanced ACC experience severe psychological and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 119 publications
0
3
0
Order By: Relevance
“…Early introduction of palliative care along with standard treatment improved quality of life, survival and psychological burden of both patients and caregivers (29). Moreover, our study revealed a negative association between large-vessel invasion and OS, which is seldom discussed with regard to prognostic prediction in most studies.…”
Section: Discussionmentioning
confidence: 67%
“…Early introduction of palliative care along with standard treatment improved quality of life, survival and psychological burden of both patients and caregivers (29). Moreover, our study revealed a negative association between large-vessel invasion and OS, which is seldom discussed with regard to prognostic prediction in most studies.…”
Section: Discussionmentioning
confidence: 67%
“…Such therapy could have an impact not only on the quality of life and perceived well-being but also on general symptoms, such as asthenia, muscle strength, bone health, and anemia ( 23 ). In addition, testosterone therapy might represent a support care against cancer-related fatigue, inappetence, cachexia, and depression ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…As regards therapy, surgical resection remains the keystone of ACC treatment.The use of Mitotane, an adrenolytic drug, in an adjuvant setting/advanced disease might prolong the relapse-free survival (49-55% in patients treated with Mitotane vs. 70-90% in control groups) [1,11,13]. First-line systemic therapy consists of Carboplatin/Cisplatin, Doxorubicin, Etoposide, and Mitotane [11].…”
Section: Discussionmentioning
confidence: 99%